Metacognitive Knowledge Predicts Success in Problem Solving Transfer - Regidor, Beverly (JPAIR Multidisciplinary Research, 2014)
Problem solving skills play a vital role in solving real life problems. This study was conducted to determine the influence of metacognitive and motivational aspects of problem solving skills to the students' success in problem solving transfer. Furthermore, it determined what aspect of the problem solving skills predicts success in problem solving transfer. The descriptive correlation method was used to determine the relationship of the metacognitive and motivational aspects of the problem solving skills and the students' success in problem solving transfer. The respondents of the study are the fourth-year high school students of Davao Central College, Philippines. There are three instruments used in the study: 1) The Metacognitive Awareness Inventory which measures their awareness in metacognitive skills such as knowledge and regulation, the 32-item Academic Intrinsic Motivation (AIM) Inventory which measures motivational aspect of the problem solving skills and lastly, the non-routinized test which measures the success in problem solving transfer. The data gathered were summarized, translated, and analyzed using the mean scores for both aspects of the problem solving skills and problem solving transfer. At 0.05 level of significance, the Pearson product moment r was used to test the significant correlation between the aspects of the problem solving skills and the success of problem solving transfer. Findings show that only the metacognitive knowledge predicts success in problem solving transfer and this is the only problem solving skills is significantly correlated to the success in problem solving transfer.
Keywords: Mathematics Education; metacognitive knowledge; predicts success; problem solving; descriptive- correlation design; Davao City; Philippines